Correlation of steam explosion severity with morphological and physicochemical characterization of soybean meal - Zeng, Qinghua; Kong, Feng; Li, Yue; Guo, Xingfeng (Frontiers in Sustainable Food Systems, 2022)
Steam explosion, a novel effective technology for cereal modification, integrating the high-temperature autohydrolysis and structural disruption, which can significantly influence the morphological and physicochemical characterization of the feedstocks. The deep knowledge of the structural changes by the treatment severity is technological demands in order to improve processing efficiency and industrial application of the feedstocks by steam explosion. In this study, the changes of morphological and physicochemical property of soybean meal induced by steam explosion were investigated, and the correlation of steam explosion severity with soybean meal final quality was analyzed. Results showed that steam explosion effectively increased the fractal dimension from 1.6553 to 1.8871, the glycinin content from 151.38 to 334.94 mg/g, and the DPPH radical scavenging activity from 28.69% to 63.78%. The gray value, color (L* and a* value), total phenols and polysaccharide content of soybean meal were reduced when the steam explosion severity was raised. Steam explosion severity had a remarkable positive correlation with the fractal dimension, DPPH radical scavenging activity. Steam explosion severity had no significant correlation with textural and adsorption property of soybean meal. This study focused on the morphological and physicochemical properties changes of soybean meal during steam explosion process, which could guide the application of steam explosion in food systems.